Scope of health worker migration governance and its impact on emigration intentions among skilled health workers in Nigeria - Kenneth Yakubu; Janani Shanthosh; Kudus Oluwatoyin Adebayo; David Peiris; Rohina Joshi (PLOS Global Public Health, 2023)
The growing trends for skilled health worker (SHW) migration in Nigeria has led to increased concerns about achieving universal health coverage in the country. While a lot is known about drivers of SHW migration, including national/sub-national government’s inability to address them, not enough is known about its governance. Underpinning good governance systems is a commitment to human rights norms, that is, principles that enshrine non-discrimination, participation, accountability, and transparency. Hence, this study was aimed at deriving a conceptual framework that captures the scope of SHW migration governance in Nigeria and the extent to which it is human rights based. To describe the scope of SHW migration governance, we conducted an exploratory factor analysis and mapped our findings to themes derived from a qualitative analysis. We also did a multivariate analysis, examining how governance items are related to migration intentions of SHWs. The scope of SHW migration governance in Nigeria can be described across three levels: Constitutional—where policies about the economy and the health workforce are made and often poorly implemented; Collective—which responds to the governance vacuum at the constitutional level by promoting SHW migration or trying to mitigate its impact; Operational—individual SHWs who navigate the tension between the right to health, their right to fair remuneration, living/working conditions, and free movement. Examining these levels revealed opportunities for collaboration through stronger commitment to human right norms. In recognising their role as rights holders and duty bearers at various levels, citizens, health advocates, health workers, community groups and policy makers can work collaboratively towards addressing factors related to SHW migration. Further evidence is needed on how human rights norms can play a visible role in Nigeria’s governance system for SHW migration.